Evaluation of the appropriateness of preoperative tests on patients undergoing elective neurosurgery - Saringcarinkul, Ananchanok; Pin-on, Pathomporn; Kongsinsukadool, Khwanhathai; Chuasuwan, Siriwan (Biomedical Sciences and Clinical Medicine, 2018)
Objective To explore the costs and benefits of 10 preoperative tests ordered for patients undergoing elective neurosurgery including resulting changes in anesthetic or surgical plans. Methods This prospective observational study of ten perioperative laboratory and radiologic tests was conducted with 344 adult patients who were scheduled for elective neurosurgery from April 2016 through March 2017. The study investigated tests ordered just prior to the surgery as well as those which had been conducted during the previous six months. The appropriateness of each test was determined based on the published guidelines of the American Society of Anesthesiologists (ASA) and the Royal College of Anesthesiologists of Thailand (RCAT). The financial costs of the tests were calculated and the patient benefits were analyzed. Results Among the 344 patients in the study, more than 50% had undergone tests including complete blood count (CBC), blood urea nitrogen and creatinine (BUN&Cr), and electrolytes within the six months prior to their surgery. Based on ASA and RCAT guidelines, in only a small percentage of cases was there a medical reason to have those tests repeated. Less than 3% of the abnormal results found in the repeated tests required further management. The test most frequently ordered appropriately, i.e., following the ASA and RCAT guidelines, was CBC. The test which was least frequently ordered in cases where the guidelines indicated it should be done was blood sugar (BS). The two tests most frequently ordered in cases where the guidelines indicated they were not necessary were prothrombin time and partial thromboplastin time (PT&PTT), and calcium, magnesium and phosphate (CaMgPO4). If all screening tests had been ordered following the ASA and RCAT guidelines, it would have resulted in a substantial reduction (up to 90%) in investigation fees for liver function test, CaMgPO4 and PT&PTT. Conclusions Preoperative investigations which are unnecessary according to ASA and RCAT guidelines are frequently ordered in our institute. A clearer understanding of the patterns of test ordering may help neurosurgeons determine which preoperative tests are appropriate and necessary.